Issues facing Christians today - Stott, John R. W (Grand Rapids, Mich. Zondervan, 2006)
Terrorism. Same-sex marriage. Debt cancellation. The AIDS pandemic. This fourth edition of Issues Facing Christians Today continues a two-decades-plus legacy of bringing important current issues under the lens of biblically informed thinking. Fully endorsed by John Stott, it has been thoroughly revised and updated by Roy McCloughry.
Keywords: Christian sociology. Church and social problems. Evangelicalism